(untitled) (Journal of the College of Basic Education, 2022)
In the last years of the rule of Shah Mohammad Reza Pahlavi, Iran witnessed a political openness as a result of international pressures that were being exerted on it because of its repressive policy towards the Iranian people in general and towards the political parties and organizations that were operating in Iran, and the most pressure came from the United States of America and its president in that The period Jimmy Carter, whose electoral slogan was the defense of human rights, as well as the desire of the United States of America to change the rules of the political game in the Middle East, In 1977, Mr. Khomeini assigned one of his own personalities with his desire to establish the Islamic Republican Party, and after extensive consultations between Mr. Khomeini’s followers and in consultation with him, especially after Mr. Khomeini settled in Paris, he announced the founding of the party in the fall of 1978, and Mr. Khomeini’s condition was that the announcement of the party remain Secretly until the victory of the Islamic Revolution. Our research covers the following: 1-The stages of establishing the party and the narratives about how to establish it 2-The most important personalities who had a role in formulating the foundations, method and principles of the party. 3-The party’s role in the presidential elections of the Islamic Republic of Iran after the victory of the Islamic Revolution. 4-The party’s position on the government of Abu al-Hasan Bani Sadr The party’s role in the elections of the Islamic Consultative Assembly